Tiger atmospheres and co-belonging in mangrove worlds - Lobo, Michele; Alam, Ashraful; Bandyopadhyay, Sumana (Environment and planning. E, Nature and space (Print), 2023)
This article adopts a place-based approach to explore tiger atmospheres in the Sundarbans, a transboundary environmental commons and major climatic hotspot in the Ganges-Brahmaputra-Meghna delta of India and Bangladesh. We argue that affective intensities of greed (lobh), fear (bhaya), respect (srodhya), trust (biswas) and empathy (karuna) sensed by the tiger subject contribute to novel theoretical as well as empirical insights into co-belonging and intersectional multispecies justice. We explore these animal atmospheres through multi-sited ethnographic research that include embodied observations, photographs, 31 in-depth interviews and focus groups with impoverished as well as racialised low-caste Hindus (Dalits/Scheduled Castes), Adivasis (Indigenous peoples) and Muslim forest-dwellers in India and Bangladesh. This attention to more-than-human geographies, animal atmospheres and subaltern stories situated in the Bengal delta unsettles macro-narratives of forest conservation and wildlife management that reduce animals to passive subjects or alternatively make them killable.